Sol^3× E^1-MANIFOLDS. (4th December 2017) - HILLMAN, J. A.
Abstract : We show that closed Sol^3× E^1 -manifolds are Seifert fibred, with general fibre the torus, and base one of the flat 2-orbifolds T, Kb, A, Mb, S(2, 2, 2, 2), P(2, 2) or D(2, 2), and outline how such manifolds may be classified.